Fundamentals of Laser‐Based Hydrogel Degradation and Applications in Cell and Tissue Engineering. Issue 24 (24th October 2017) - Pradhan, Shantanu; Keller, Keely A.; Sperduto, John L.; Slater, John H.
Abstract: The cell and tissue engineering fields have profited immensely through the implementation of highly structured biomaterials. The development and implementation of advanced biofabrication techniques have established new avenues for generating biomimetic scaffolds for a multitude of cell and tissue engineering applications. Among these, laser‐based degradation of biomaterials is implemented to achieve user‐directed features and functionalities within biomimetic scaffolds. This review offers an overview of the physical mechanisms that govern laser–material interactions and specifically, laser–hydrogel interactions. The influences of both laser and material properties on efficient, high‐resolution hydrogel degradation are discussed and the current application space in cell and tissue engineering is reviewed. This review aims to acquaint readers with the capability and uses of laser‐based degradation of biomaterials, so that it may be easily and widely adopted. Abstract : The fundamental mechanisms, based on laser and hydrogel properties that mediate laser‐based hydrogel degradation are discussed here, and the current application space in cell and tissue engineering is presented. The aim is to acquaint readers with the capabilities and limitations of laser‐based hydrogel degradation so that it may be easily and widely adopted for biofabrication and other applications.